Adjectives in Lubukusu - Wasike, Aggrey (My University, 2018)
The lexical category of adjectives is proposed to be universal, but its realization varies across languages. In languages such as English, there is a clearly distinct category of adjectives. But in other languages the category of adjectives is not entirely distinct morphologically and syntactically from nouns and verbs. In this paper I show that there is a striking resemblance between adjectives and nouns in Lubukusu. In addition, stage-level predicate meanings are expressed by use of verbs rather than adjectives. Because of these facts, it is tempting to adopt an analysis that reduces Lubukusu adjectives to either nouns or verbs. However, I argue that there is not sufficient evidence to support such an analysis. Lubukusu has true adjectives in spite of the associated nominal and verbal characteristics. A verbal characteristic such as expressing adjectival meanings by use verbs is similar to languages such Mohawk and Vaeakau-Taumako. But there are significant differences between these languages and Lubukusu with regards to this verbal characteristic.
Keywords: Lubukusu; Adjectives; languages